Sigma Notation In Inductive Proofs

When using proof by induction to demonstrate the result of a sum, we can often use sigma notation to make these proofs more concise. Suppose we want to show that

n=1N1(2n1)(2n+1)=N2N+1\sum_{n=1}^{N}{\frac1{(2n-1)(2n+1)}} = \frac{N}{2N+1}

To use proof by induction to demonstrate this, we need to:

  1. Establish the base case,
  2. Demonstrate the inductive step

If we consider the most general case of this problem, we are trying to show that

n=1Nf(n)=g(N)\sum_{n=1}^{N}{f(n)} = g(N)

where f(n)f(n) are the terms of our series, and g(N)g(N) is an analytic expression which we want to show can be used to evaluate the value of the series directly. To prove that this expression hold for all NNN \in \N, we need to show that it holds for N=1N = 1, which means we need to show that

n=11f(n)=g(1)f(1)=g(1)\begin{aligned} \sum_{n=1}^{1}{f(n)} &= g(1) \\ f(1) &= g(1) \\ \end{aligned}

And then for our inductive step, we assume that the expression holds for N=kN = k, and we need to prove it for N=k+1N = k + 1. Since the series between these two cases differ only in the final term, we typically use the following approach

n=1k+1f(n)=n=1kf(n)+f(k+1)n=1k+1f(n)=g(k)+f(k+1)\begin{aligned} \sum_{n=1}^{k+1}{f(n)} &= \sum_{n=1}^{k}{f(n)} + f(k+1) \\ \sum_{n=1}^{k+1}{f(n)} &= g(k) + f(k+1) \\ \end{aligned}

From here, if we can then show that g(k)+f(k+1)=g(k+1)g(k) + f(k+1) = g(k+1), then we are able to conclude that

n=1k+1f(n)=g(k+1)\sum_{n=1}^{k+1}{f(n)} = g(k+1)

which then completes our proof.

...

Log in or sign up to see more